"Fake News" and Emerging Online Media Ecosystem: An Integrated Intermedia Agenda-Setting Analysis of the 2016 U.S. Presidential Election. (March 2020) - Guo, Lei; Vargo, Chris
This study examined how fake news, misinformation, and satire, affected the emerging media ecosystem during the 2016 U.S. presidential election through an integrated intermedia agenda-setting analysis, which studies broad attributes and myopic stories and events. A computer-assisted content analysis of millions of news articles was conducted alongside a qualitative analysis of popular news headlines and articles. The results showed that websites that spread misinformation had a fairly close intermedia agenda-setting relationship with fact-based media in covering Trump, but not for the news about Clinton. Satire websites barely interacted with the agenda of other media outlets. Overall, it seemed that rather than playing a unique agenda-setting role in this emerging media landscape, fake news websites added some noise to an already sensationalized news environment.